PERILAKU HIDUP BERSIH DAN SEHAT SAAT PANDEMIK COVID-19 DI DESA SUNGAI RAYA - Agus Alamsyah; Ikhtiaruddin Ikhtiaruddin; Muhamadiah Muhamadiah; Yuyun Priwahyuni; Christine Vita Gloria Purba (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2020)
Clean and healthy living behavior ( PHBS ) is done at health behavior all of consciousness resulting family members or family to help themselves in the health and could actively in the berperanaktif in health and health activities in the community .The village of sungai raya 347 households consisting all of which have different characteristics and health problems .In the village of sungai raya has never done a survey of phbs at the stage of households covid-19 mainly during the pandemic , so it is not known how the phbs him .Research objectives relating to implementation mengtahui want healthy life at the stage of the community at the time in the village of sungai raya covid-19 old in the year 2020. Quantitative methods used is descriptive. It is a whole population in phbs household 347. households and the restSample 90 families were taken by proportional. random samplingAnalysis using univariat uses software and computerized.The results of the study which are healthy life in the village of sungai raya not achieve the target set by the ministry of health in 70 %, so an active role in the promotion of health and the further is done by penyuluhan-penyuluhan phbs and visits directly to the communities to promote healthy life to people in the village of Sungai Raya.